Pengembangan Profesionalitas BerbasisTeknologi Digital bagi Guru di daerah Kepulauan “Pelatihan Media Pembelajaran (Quizziz, Blokked dan Worwall) di SMP Negeri 43 Maluku Tengah” - Jenny Koce Matitaputty; Tama Maysuri; Kesya Bitalessy; Eklesya Hitijahubessy; Susanti Sairkelu (Jurnal Informasi Pengabdian Masyarakat, 2026)
This community service activity aims to answer one of the important parts of the island education and disaster mitigation course in the history education study program of FKIP Unpatti, namely improving the professionalism of teachers in the island region with a sub-chapter on digitalization of teachers in the island region. It is hoped that the implementation of this practicum and community service can add insight to partners with knowledge and skills to teachers of SMP 34 Central Maluku in the use of digital technology (Quizizz, Bloked, Wordwall) as a medium in learning. The target that the implementer wants to achieve in this activity is to increase the insight of knowledge and skills to teachers as activity partners, and it is hoped that this knowledge and skills can be applied in the learning process, so that the skills of using digital technology-based learning applications (Quizizz, Bloked, Wordwall) can be applied in learning to students in the island region. This training activity went smoothly and was able to achieve the expected targets and outcomes. The implementation method starts from the activity plan, namely preparation, implementation, and evaluation activities. This training activity will begin with material related to technology applications (Quizizz, Bloked, Wordwall) in learning, an introduction to each feature, registration, and simulations of how to create them, along with mentoring and testing of each teacher's work for each application. The results of this community service activity, through practical activities in this course, demonstrate that the digital technology media training (Quizizz, Bloked, Wordwall) for teachers in the island region, particularly at SMP 34 Central Maluku, has made a significant contribution. Testimonials and questionnaires indicate 100% teacher satisfaction and readiness to apply the use of (Quizizz, Bloked, Wordwall) in teaching.